2016
DOI: 10.1007/s13679-016-0205-z
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Workplace Weight Management Interventions: a Systematic Review

Abstract: A systematic review was conducted of randomized trials of workplace weight management interventions, including trials with dietary, physical activity, environmental, behavioral, and incentive-based components. Main outcomes were defined as change in weight-related measures. Keywords related to weight management and workplace interventions were used to search relevant databases, and 23 eligible studies were reviewed in detail using a data extraction form and quality assessment checklist. The trials were conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 40 publications
4
33
0
1
Order By: Relevance
“…In addition, to our knowledge this analysis provides the first evidence that videoconference delivery of a group WL program results in WL that is comparable with in‐person program delivery. Furthermore, consistent with results from a previous RCT of this WL program , and contrary to reports from other programs , this analysis also found that %WL in worksites was greater than in community groups. An additional finding was that %WL was greater at 11 weeks for individuals enrolling in January or February compared to later in the year, which is, to our knowledge, the first report of seasonal influences on WL program effectiveness.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, to our knowledge this analysis provides the first evidence that videoconference delivery of a group WL program results in WL that is comparable with in‐person program delivery. Furthermore, consistent with results from a previous RCT of this WL program , and contrary to reports from other programs , this analysis also found that %WL in worksites was greater than in community groups. An additional finding was that %WL was greater at 11 weeks for individuals enrolling in January or February compared to later in the year, which is, to our knowledge, the first report of seasonal influences on WL program effectiveness.…”
Section: Discussionsupporting
confidence: 89%
“…These results confirm the exceptional effectiveness of the iDiet program in worksites, as suggested previously , and further suggest that worksite videoconference programs could become a routine and effective way to improve worksite health. These positive findings contrast with the relatively low WL achieved by other programs in worksites , and further work is needed to explore reasons for between‐program differences in WL in worksites. In relation to this suggestion, it should also be noted that differences in payment structure are unlikely to be a complete explanation, because %WL at 11 weeks in this analysis did not vary by program payment structure, even though complete weight reporting was highest when employee payments were linked to an incentive (usually payments for completing benchmarks such as meeting attendance).…”
Section: Discussionmentioning
confidence: 73%
“…Evidence also suggests that adults' home neighborhood recreation environment (e.g., the presence of parks, public recreation facilities, or gyms near home) is less related to adults' physical activity than other aspects of the home neighborhood (e.g., walkability) and that the neighborhood recreation environment may influence children's more than adults' physical activity . Considerable evidence exists regarding worksite interventions for adult weight management , although many of the interventions have taken an individual‐focused rather than environmentally focused approach (for exceptions, see Fernandez et al ). Less is known about whether and which aspects of the worksite environment may impact an individual's ability to initiate or sustain healthy behaviors while engaged in active weight loss or maintenance attempts.…”
Section: Other Environmental Constructs and Measures Consideredmentioning
confidence: 99%
“…According to the existing literature, workplace physical activity and nutrition interventions that involved counseling, education and on-site group activities have generally shown significant changes in employee sedentary and eating behavior, improving physical and mental health and a positive return on investment by reducing health care costs as well as overall absenteeism (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%